Antidiabetic effect of new chromane isolated from Dillenia indica L. leaves in streptozotocin induced diabetic rats. (April 2016) - Kaur, Navpreet; Kishore, Lalit; Singh, Randhir
Highlights: Alcoholic extract of D. indica yielded a new chromane 3, 5, 7, -Trihydroxy-2-(4-hydroxy-benzyl)-chroman-4-one. Compound exhibited potential antioxidant activity. Chromane isolated from D. indica possessed antioxidant and antidiabetic activity and could be a therapeutic agent for regulating several pharmacological targets for management of diabetes. Abstract: The chemical constituents of Dillenia indica were isolated together with evaluation of their antioxidant and antidiabetic activity. Alcoholic extract of D. indica (DAE) was subjected to column chromatography for the isolation of compounds and it yielded a new chromane 3, 5, 7, -trihydroxy-2-(4-hydroxybenzyl)-chroman-4-one. The structure was determined by 1H, 13C-NMR and ESIMS. DAE (100, 200 and 400 mg/kg) and chromane (5 and 10 mg/kg) were administered to streptozotocin (STZ) (50 mg/kg) induced diabetic rats to assess their effect on fasting blood glucose, serum insulin and lipid levels. Oral administration of chromane and DAE significantly attenuated the elevated fasting blood glucose, lipid levels and oxidative stress. The results indicated that DAE and chromane isolated from D. indica possessed antioxidant and antidiabetic activity and could be a therapeutic agent for regulating several pharmacological targets for management of diabetes.